Pharmaceutical powder production by spray-freeze-drying technique : design and optimization of experimental parameters. - Ng, Mabel Li Ling. (2010)
Spray-freeze-drying (SFD) has emerged in the last decade as a manufacturing technique for proteins and other heat-sensitive compounds. However, its application to nano-medicines has not been explored. Hence, the purpose of this project is to develop and optimize the SFD conditions for the production of nano-aggregates.